2020
DOI: 10.2196/16898
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Smartphone App for Caregivers of Children With Atopic Dermatitis With Caregivers, Health Care Professionals, and Digital Health Experts: Participatory Co-Design

Abstract: Background Smartphone apps could support patients and caregivers in disease self-management. However, as patients’ experiences and needs might not always align with clinical judgments, the eliciting and engaging of perspectives of all stakeholders in the smartphone app design process is of paramount importance. Objective The aims of this study are to better understand the needs of and challenges facing caregivers and health care professionals (HCPs) who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The use of co-design in caregiver research is growing and aligns well with other emerging work. Our strategy was to equip our participants with a variety of different stakeholder viewpoints through discussion before completing questionnaires [ 32 ]. Such co-design was successfully used previously by Xu et al [ 32 ] when designing an app for caregivers of children with atopic dermatitis to develop functionalities such as login, disease diary, journal, chatbot, forum, and disease monitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of co-design in caregiver research is growing and aligns well with other emerging work. Our strategy was to equip our participants with a variety of different stakeholder viewpoints through discussion before completing questionnaires [ 32 ]. Such co-design was successfully used previously by Xu et al [ 32 ] when designing an app for caregivers of children with atopic dermatitis to develop functionalities such as login, disease diary, journal, chatbot, forum, and disease monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Our strategy was to equip our participants with a variety of different stakeholder viewpoints through discussion before completing questionnaires [ 32 ]. Such co-design was successfully used previously by Xu et al [ 32 ] when designing an app for caregivers of children with atopic dermatitis to develop functionalities such as login, disease diary, journal, chatbot, forum, and disease monitor. As part of this work, participants helped us to identify several different barriers and enablers to physical activity from the home, including lack of time, finding a way to recognize efforts, and being able to conduct activities safely.…”
Section: Discussionmentioning
confidence: 99%
“…Empowering users has radically changed the way user and customer value is created and transferred; therefore, many organizations have consequently set out business concepts based on the recognition of these changes and the opportunities they bring about. By adopting technology solutions, health organizations and clinical services have started to empower users in contexts such as self-management treatments (Goldchmit et al, 2021), healthcare education (Xu et al, 2020), care for vulnerable users (Gill et al, 2019) and developing peer-to-peer online communities (Amann and Rubinelli, 2017). Chen et al (2014) suggest that e-health as a service innovation needs to consider a wide variety of users, including patients, service recipients and service providers, when it comes to the formation of commercially viable business concepts.…”
Section: User Innovation In Healthcaretechnologymentioning
confidence: 99%
“…This focus group study is part of a qualitative participatory co-design process. Co-design methodology in healthcare research has been found to engage with all the participants, allowing them to "express their creativity and … to articulate the root of the clinical problems" (17). It can help to identify, "tension between the professional agenda driven primarily by cost-effectiveness and the patient agenda that prioritises the process of care" (18).…”
Section: Co-design Processmentioning
confidence: 99%